ROLE OF COMPETENCE-BASED APPROACH TO MANAGAMENT IN IT-COMPANIES - Vasily S. Kasyanov; Kseniya N. Balastrova (Вестник Северо-Кавказского федерального университета, 2022)
The article stated premise of the concept of competence-based approach in terms of development of informatization of all spheres of society. We consider the problems of information management in the functioning of IT companies. The analysis of foreign and domestic experience highlights the key elements of the innovation structure and to determine their role in terms of the leading companies in the IT industry. We propose a list of corporate competencies that form the basis of the competence of management, and their relationship with the most common technology innovation.